Eksperimen Sains Sederhana di KB-TKIT Salman Al-Farisi 2 Yogyakarta - Ratih Purwanti (Permata Indonesia, 2023)
Early Childhood Education (PAUD) is essentially education that is held with the aim of facilitating the growth and development of children as a whole or emphasizing the development of all aspects of the child's personality. Therefore PAUD provides an opportunity for children to develop their personality and potential to the fullest. Children have a very high curiosity. This curiosity needs to be facilitated by adults, including parents/tutors/teachers who function as children's teachers. Children can learn anything from an early age, including learning science. Learning science from an early age begins by introducing nature and the environment. This will enrich the child's experience. Children learn to experiment, explore, and investigate their surroundings. This Community Service Activity (PkM) aims to improve children's skills in honing the ability to think about simple science events and provide education to children about simple experiments. This activity is carried out in the form of simulations and direct practical assistance to TK- KBIT Salman Al-Farisi 2 Yogyakarta. The first experiment was blowing up a balloon with a bottle. The second experiment is to make rainbow colors in a bottle and the third is a lava lamp. The result of this activity is that participants can carry out simple science experiments and gain scientific knowledge from the experiments carried out Keywords: experiments, childhood, science